Crafting infinity : reworking elements in Irish culture - Cornish, Rory T.; Quintelli-Neary, Marguerite, 1953- (Cambridge Scholars Publishing, 2012)
Crafting Infinity is a multi-disciplinary collection of essays that investigates how aspects of traditional Irish culture have been revised, retooled, and repackaged in the interest of maintaining the integrity of Irish myth tales, artistic values, spiritual foundations, and historic icons. From perspectives on early Irish Christianity to national mythology, traditional Irish music, Irish history represented in film, literary inventiveness, and evidence of the Irish diaspora, this study exami ...